Assessing the Concept of Poverty Concentration in HOPE VI. - Welch, Meghan. (2017)
Abstract: This thesis examines the theory and application of poverty concentration and deconcentration within public housing's HOPE VI program. Negative resident behaviors, such as crime, unemployment, low education attainment and teenage pregnancy are posited to be symptoms of "poverty concentration" or the grouping of low-income people in public housing. Poverty concentration, along with other public housing challenges, has prompted a reform of housing poor people. Through the dispersal of public housing residents across lower poverty communities and the rehabilitation of public housing projects into housing for a range of incomes, the $7 billion HOPE VI program advances this reform and aims to do more than simply administering housing. Theoretically, a mixed income environment will improve the social and economic stability of public housing residents by increasing interaction and connection to positive social networks, role models, institutions, and mainstream opportunities. However, the absence of a causal relationship between poverty, its concentration, its negative effects on life outcomes, and socialization mechanisms, challenges such theories. The assessment suggests several important implications and critiques about the concept of poverty concentration, and the strategy of poverty deconcentration as advanced by the HOPE VI program.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: James Jennings.; Committee: Laurie Goldman.; Keyword: Public policy.